2021
DOI: 10.3390/ijms22042094
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response of Mouse Embryonic Fibroblasts Exposed to Polystyrene Nanoplastics

Abstract: Polystyrene (PS) nanoplastic exposure has been shown to affect the viability of neuronal cells isolated from mouse embryonic brains. However, the viability of mouse embryonic fibroblasts (MEFs) was not affected although PS nanoplastics accumulated in the cytoplasm. It is currently unknown whether MEFs do not respond to PS nanoplastics or their cellular functions are altered without compromising viability. Here, we found that PS nanoplastics entered the cells via endocytosis and were then released into the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Conversely, 100 nm particles even stimulated cell viability to 121.5 ± 6.9% at 10 µg/mL. These results correlate well with a recent study where mouse embryonic fibroblasts were subjected to 100 nm polystyrene beads, which also did not affect the viability and proliferation of the cells [ 32 ]. However, other polystyrene beads of other sizes were not investigated using fibroblasts cell cultures, therefore we indicate here that the size-dependent effects are likely and need to be studied in more detail in the future.…”
Section: Resultssupporting
confidence: 90%
“…Conversely, 100 nm particles even stimulated cell viability to 121.5 ± 6.9% at 10 µg/mL. These results correlate well with a recent study where mouse embryonic fibroblasts were subjected to 100 nm polystyrene beads, which also did not affect the viability and proliferation of the cells [ 32 ]. However, other polystyrene beads of other sizes were not investigated using fibroblasts cell cultures, therefore we indicate here that the size-dependent effects are likely and need to be studied in more detail in the future.…”
Section: Resultssupporting
confidence: 90%
“…The data of Nie et al indicated the upregulation of Atg7, Atg5, and LC3-II protein expression and the fluorescence intensity of GFP-LC3 in SH-SY5Y cells after exposure to 60 nm PS-NPs [ 34 ]. Exposure to 100 nm PS-NPs could increase LC3 autophagic pathway activation in mouse embryonic fibroblasts (MEFs) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…While it is unknown if these compounds leak straight into living tissues, some additives like Bisphenol A have been discovered to be consumed by marine biota (Chen et al, 2020;Koelmans et al, 2014), Absorption of this leachate frequently used in lining food and beverage cans, can induce endocrine problems and adversely affect human health (Ryan, 2015). In particular, associated health risks may include, cytotoxicity (Gopinath et al, 2021), neurotoxicity (Han et al, 2021;Varsou et al, 2021), immunotoxicity, reproductive toxicity (He et al, 2021), or even carcinogenicity (Gao et al, 2021). Yip et al (2022) have tested and predicted the possibility of MNPs transfer from mother to offspring.…”
Section: On Living Organismsmentioning
confidence: 99%